Analysis Measurement of Quality Service Hotel with Approach of Method Servqual - Umar Wiwi (Department Industrial Engineering, University of Muhammadiyah Malang, 2008)
Hotel UMM Inn is a kind of hotel in Malang at Muhammadiyah Malang University. Hotel UMM Inn in university Commitment of service quality that orients to customer in main prerequisite in supporting a bussines success, especially to service industry. This is caused a service quality is largely depending from who how the service is given. In A Quarter of hotel bussines in malang and the coming of Motel, Wisma and Villa. In this research, method which used in measurement of service quality is method of Servqual. Assessment of quality of service by using method of Servqual reckoned from by difference between expectation and perception of service. Data-Processing taken is calculation of expectation score and perception of custumer, calculation of service gap score, determination of service quality factor and map service variable into Customer Window. Result of this research indicate that score of is quality of hotel service there are 7 valuable service variable of negativity like Hygiene of hotel UMM Inn, availibility of clean water in toilet, accident insurance guarantee and the others. Result of from Customer Window indicate that service variable which must be made by especial priority (Here Concentrate) which must fulfill by hotel management of UMM Inn that is clean of Hygiene of hotel UMM Inn, availibility of clean water in toilet, and departure and the others.